Childhood cognitive ability and its relationship with anxiety and depression in adolescence - Weeks, Murry; Cameron, Wild; Ploubidis, George; Naicker, Kiyuri; Cairney, John; North, Rebecca; Colman, Ian (Université d'Ottawa | University of Ottawa, 2014)
BACKGROUND: Childhood cognitive ability may have protective effects against internalizing symptoms in adolescence, although this may depend on the time of symptom assessment and child gender. Also, the effects of childhood stressors on adolescent internalizing symptoms may be moderated by childhood cognitive ability. METHODS: The sample included 4405 individuals from the Canadian National Longitudinal Study of Children and Youth (NLSCY). Between ages 4-5 and 10-11, children completed a test of verbal ability and scholastic aptitude and a series of mathematics computation tests. Internalizing symptoms were assessed via self-reports at ages 12-13 and 14-15. RESULTS: Greater cognitive ability was generally associated with decreased odds of internalizing symptoms at age 12-13. However, greater cognitive ability generally increased, or had no effect on, the odds of internalizing symptoms at age 14-15. Some of the effects of childhood cognitive ability varied with child gender. Also, childhood cognitive ability attenuated the effects of family dysfunction and chronic illness throughout childhood on subsequent internalizing symptoms. LIMITATIONS: These data are largely subject to some degree of reporting bias, the tests of cognitive ability are limited and may not represent overall cognitive ability, and there may be intermediary variables that account for the relationship between childhood cognitive ability and adolescent internalizing symptoms. CONCLUSION: Results suggest that programs attempting to increase early cognitive skills may be particularly beneficial for girls. Also, an increased focus on cognitive skills may attenuate the negative effects of some stressors on subsequent anxious and depressive symptoms, regardless of child gender.
Keywords: Anxiety; Depression; Adolescence; Epidemiology; Cognitive ability